Human Factors and Road Traffic Safety: An Inquiry into The Causes of Upsurge in Road Traffic Accidents in Harare Metropolitan Province, Zimbabwe - Munyaradzi Chibaro; Shakerod Munuhwa; Cynthia Mupfiga; Farai Chibharo Farai (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The study assessed the effects of human factors on road traffic safety in minimizing road traffic accidents in Harare Metropolitan, Zimbabwe. The objectives of this study were to examine the relationship between human factors and road traffic accidents on Harare's roads. Human factors which were tested ranges from improper age of drivers who tend to overtake and overspeed recklessly, over speeding, alcohol drinking, corruption and failure to maintain vehicles as a moderating variable. The study was informed by post positivism philosophy since this philosophy enables greater engagement between the researcher and research participants. The study employed cross-sectional descriptive survey and data was gathered from respondents using structured questionnaires. Cronbach's alpha (α) was used to assess data reliability. Five hypotheses that passed the validity and normalcy tests were examined using structural equation modelling. For data analysis, licensed SPSS® version 21 and licensed AMOS® version 21 were utilized. The statistical analysis and results demonstrated a moderate correlation between the independent variables (speeding, drunken driving, corruption, age, and the moderating effect of vehicle maintenance on traffic safety). The analysis showed that young, inexperienced drivers are 2.5 times more likely to crash than more experienced motorists when their blood alcohol level is 0.05 g/dl or higher. Unsafe road vehicles, unlicensed drivers, overloading, speeding, and drunk driving are listed as the most frequent crimes leading to road traffic accidents. The findings showed that violating traffic regulations and engaging in reckless driving by young inexperienced drivers both contribute to the occurrence of road traffic accidents (RTAs). The findings of this study however, concluded that excessive speeding and drunk driving while driving have been identified as the worst human behavior causing accidents in Zimbabwe but vehicle maintenance plays a significant role is the reduction of road traffic accidents. The study came to the conclusion that it is necessary to enforce the speed limit and deploy speed cameras at significant intersections and problem areas. Key words: Road traffic safety, road traffic accidents, vehicle maintenance, human behavior, drunk driving, corruption